Home Activities of Students to Counter Psychological Disturbances during COVID-19 Pandemic - Cherish Kay L. Pastor; Caren C. Orlanda-Ventayen; Timothy Joshua M. Ventayen; Lemuel M. Ventayen; Randy Joy M. Ventayen (International Journal of Psychosocial Rehabilitation, 2020)
The effects of coronavirus that cause COVID-19 have been felt all over world. All institutions in Luzon, Philippines are closed due to the suspension of classes. The College of Business and Public Administration (CBPA) of Pangasinan State University, Lingayen Campus, initiated a survey to determine the leisure activities conducted by student at home and their preferences to counter emotional and psychological disturbances during COVID-19 Pandemic. An open-ended question was created using online forms, and class group chats through messenger were used to float the link of the questionnaire and to gather qualitative responses. Convenience sampling was used in determining the respondents and the answers were tabulated using Google Sheet. The result shows that students use messaging services, surfing the internet and social media in order to counter the boredom that could lead to psychological problems. While students understand that those leisure preferences may not hinder loneliness and mental illness, students are finding other activities that contribute in combatting the negative mindset during COVID-19.